Fame Lover - Hakimov, Kamal (European Journal of Life Safety and Stability (2660-9630), 2022)
"Martin Eden" by Jack London in the article novel, the fate of the characters, views on life, abysses in human nature, complex mental states, happiness, freedom of spirit, flexibility of views, etc. It is important not to forget that it is a natural phenomenon. It should also be noted that since the reality in the article is described in the style of a story, the incomplete verb "was" was felt a lot.